MULTICULTURAL VALUES IN INDONESIAN ENGLISH TEXTBOOK - Mardiana, Wiwik; Susanti, Ika; Fadillah, Alfina Nur (Indonesian language and literature education program Majapahit Islamic University, 2023)
The aim of this study is to investigate the representation of multicultural values in senior high school English textbooks and elucidate how these values align with the eight characters of education. The theoretical framework guiding the analysis of the textbooks is based on Fairclough's theory of critical discourse analysis. The findings unveiled the presence of four core multicultural values within the textbooks, encompassing (1) Acceptance and appreciation of cultural diversity, (2) Respect for human dignity and universal human rights, (3) Responsibility to the world community, and (4) Respect for the earth. Additionally, the examination identified six character education values grounded in Pancasila, namely (1) Religious, (2) Tolerance, (3) Patriotism, (4) Friendly/communicative, (5) Environmental care, and (6) Social care. Keywords: multicultural, discourse analysis, visual analysis